COME ASPECTS OF SOCIAL PARTNERSHIP IN THE DEVELOPMENT OF EDUCATION (TAMADDUN NURI JURNALI, 2025)
The article notes that the most successful implementation of the processes of reproduction of competitive specialists and the development of social partnership is seen precisely within the framework of the concept of lifelong education.